2003
DOI: 10.1159/000070957
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High-Dose Intravenous Immunoglobulin Therapy in Stevens-Johnson Syndrome: A Retrospective, Multicenter Study

Abstract: Background:Stevens-Johnson syndrome (SJS) is a severe cutaneous drug reaction associated with considerable morbidity, possible transition to toxic epidermal necrolysis (TEN) and death in certain cases. Objective: To determine whether treatment with high-dose IVIG in SJS patients may improve outcome. Methods: Data from 12 patients (collected between January 1997 and November 2000 from7 university dermatology centers in Europe and North America) diagnosed with SJS according to a recent consensus definition was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 15 publications
1
43
0
1
Order By: Relevance
“…Treatment with IVIg resulted in a more rapid cessation of epidermal detachment and a survival rate of 88%. The authors subsequently recommended a dose of 1 g/kg/daily for 3 days [143]. Studies have also demonstrated benefit when investigators have compared the rates of mortality following the use of IVIg with the pre-treatment estimate using SCORTEN.…”
Section: Intravenous Immunoglobulin (Ivig)mentioning
confidence: 99%
“…Treatment with IVIg resulted in a more rapid cessation of epidermal detachment and a survival rate of 88%. The authors subsequently recommended a dose of 1 g/kg/daily for 3 days [143]. Studies have also demonstrated benefit when investigators have compared the rates of mortality following the use of IVIg with the pre-treatment estimate using SCORTEN.…”
Section: Intravenous Immunoglobulin (Ivig)mentioning
confidence: 99%
“…A estek jelentôs részében az IVIG kezelés mellett gyermekpopulációban a morbiditási és mortalitási arány, valamint a hospitalizáció idôtartalmának csökkenését, a reepithelizáció folyamatának felgyorsulását észlelték, mellékhatások ritkán fordultak elô (14,21,30,(32)(33)(34)(35).…”
Section: Megbeszélésunclassified
“…French reviewed nine studies in which 10 or more patients were treated and seven of the nine showed highly significant reductions in mortality [43]. The largest study included in that review was a prospective study of 48 cases with SJS treated at a mean dose of 0.6 g kg -1 day -1 for 4 days with a survival of 88% [44]. However, the review suggested that in general 1 g kg -1 day -1 for 3 days is recommended.…”
Section: Intravenous Immunoglobulin (Ivig)mentioning
confidence: 99%